# Find the inverse of the function y = 2x^{2} + 2.

An inverse function is the reverse of an original function with inverse mapping. They have many interesting applications in various fields like calculus and algebra.

## Answer: The inverse of the function y = 2x^{2} + 2 is f^{-1}(x) = √(x - 2) / √2.

Let us proceed step by step to find the solution.

**Explanation:**

From the given function

y = 2x^{2} + 2

Since we are finding the inverse, we have to interchange the variables.

Therefore, x = 2y^{2} + 2

Now, if we simplify the given equation further, we get:

x - 2 = 2y^{2}

(x - 2) / 2 = y^{2}

Now, taking square root on both sides:

y = √(x - 2) / √2

Now, after replacing y with f^{-1}(x), we get:

f^{-1}(x) = √(x - 2) / √2